Пошаговое объяснение:
0,8-0,5(х+3)=2-0,2(х-6)
0,8 - 0,5x - 1,5 = 2 - 0,2x + 1,2
-0,7 - 0,5x = 3,2 - 0,2x
0,5x - 0,2x = -0,7 - 3,2
0,3x = -3,9
x = -3,9 : 0,3
x = -13
х = -13
0,8 - 0,5(х + 3) = 2 - 0,2(х - 6)
0.8 - 0.5х - 1.5 = 2 - 0.2х + 1.2
-0.3х = 1.5 + 1.2 - 0.8 + 2
-0.3х = 3.9
-3х = 39
Пошаговое объяснение:
0,8-0,5(х+3)=2-0,2(х-6)
0,8 - 0,5x - 1,5 = 2 - 0,2x + 1,2
-0,7 - 0,5x = 3,2 - 0,2x
0,5x - 0,2x = -0,7 - 3,2
0,3x = -3,9
x = -3,9 : 0,3
x = -13
х = -13
Пошаговое объяснение:
0,8 - 0,5(х + 3) = 2 - 0,2(х - 6)
0.8 - 0.5х - 1.5 = 2 - 0.2х + 1.2
-0.3х = 1.5 + 1.2 - 0.8 + 2
-0.3х = 3.9
-3х = 39
х = -13